2018
DOI: 10.1111/pala.12399
|View full text |Cite
|
Sign up to set email alerts
|

Archosauromorph extinction selectivity during the Triassic–Jurassic mass extinction

Abstract: Many traits have been linked to extinction risk among modern vertebrates, including mode of life and body size. However, previous work has indicated there is little evidence that body size, or any other trait, was selective during past mass extinctions. Here, we investigate the impact of the Triassic–Jurassic mass extinction on early Archosauromorpha (basal dinosaurs, crocodylomorphs and their relatives) by focusing on body size and other life history traits. We built several new archosauromorph maximum‐likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 77 publications
2
24
0
Order By: Relevance
“…In this context, we acknowledge that the inclusion in our analyses of larger non-crocodyliform crocodylomorphs, such as Carnufex carolinensis (~ 3 m [172]), might change our results. Apart from these differences, both Turner & Nesbitt [49] and a more a more recent study [50] found no significant influence of crocodylomorph body size on extinction at the T–J boundary, which is consistent with our analyses. Thus, at the moment we do not have empirical or statistical evidence to demonstrate selectivity of body sizes in crocodylomorphs during the end-Triassic extinction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, we acknowledge that the inclusion in our analyses of larger non-crocodyliform crocodylomorphs, such as Carnufex carolinensis (~ 3 m [172]), might change our results. Apart from these differences, both Turner & Nesbitt [49] and a more a more recent study [50] found no significant influence of crocodylomorph body size on extinction at the T–J boundary, which is consistent with our analyses. Thus, at the moment we do not have empirical or statistical evidence to demonstrate selectivity of body sizes in crocodylomorphs during the end-Triassic extinction.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, studies quantitatively investigating macroevolutionary patterns of body size in crocodylomorphs have been restricted to particular time periods (e.g., Triassic-Jurassic body size disparity [49, 50]) or clades (e.g., metriorhynchids [51]), limiting broader interpretations. For instance, the impact of environmental temperature on the growth and adult body size of animals has long been acknowledged as an important phenomenon [4] and has been considered to have a significant influence on the physiology and distribution of extant crocodylians [52, 53].…”
Section: Introductionmentioning
confidence: 99%
“…A key question in paleobiology concerns whether mass extinctions selectively remove taxa based on their trait values or whether extinction is random with regard to traits. To this end, previous phylogenetic approaches to detecting extinction selectivity at mass extinctions have used pGLS models to test whether surviving and extinct lineages differ significantly in trait values (Friedman 2009;Puttick et al 2017;Allen et al 2019). pGLS models are appropriate in this context to correct for nonindependence of residuals in the regression as a result of shared phylogenetic history (Felsenstein 1985), but we show that pGLS models are not able to correctly support the hypothesis that trait values differ in extinct lineages compared to surviving lineage trait values (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Empirical studies have demonstrated cases where mass extinctions acted both selectively and nonselectively with regard to particular traits (Foote 1993;Roy 1996;Lockwood 2004;Erwin 2007;Halliday and Goswami 2016). Phylogenetic comparative studies indicate that there is trait selectivity on some groups, such as vascular plants (Green et al 2011), but there is little evidence to link traits and extinction susceptibility during mass crises in the fossil record (Friedman 2009;Puttick et al 2017;Allen et al 2019). Many studies reveal a phylogenetic signal of extinction (Hardy et al 2012;Harnik et al 2014;Krug and Patzkowsky 2015;Puttick et al 2017;Soul and Friedman 2017), without demonstrating links to trait selectivity.…”
mentioning
confidence: 99%
“…Functions to facilitate analyses of trait selectivity of mass extinction in the fossil record (Allen, Stubbs, Benton, & Puttick, 2018;Puttick et al, 2017). Also functions to add fossils to ultrametric phylogenies.…”
Section: Utility Functionsmentioning
confidence: 99%